2012
DOI: 10.3109/10903127.2012.717166
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital Point-of-Care Testing for Troponin: Are the Results Reliable?

Abstract: When used in a moving ambulance, the POC device provided results of cardiac troponin I assays that were highly correlated to the results when the device was used in the ED. The feasibility, practicality, and clinical utility of prehospital use of POC devices must still be assessed. Key words: point-of-care systems; prehospital emergency care; troponin; reliability of results; ambulances; myocardial infarction; chest pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…Sex disparities in favour of male patients have also been reported in a study of EMS stroke recognition [21]. The introduction of point-of-care testing has been shown to be feasible in the EMS [22] and may aid further in complex assessments.…”
Section: Transported and Non-transported Patientsmentioning
confidence: 93%
“…Sex disparities in favour of male patients have also been reported in a study of EMS stroke recognition [21]. The introduction of point-of-care testing has been shown to be feasible in the EMS [22] and may aid further in complex assessments.…”
Section: Transported and Non-transported Patientsmentioning
confidence: 93%
“…Many studies have been performed that show the time to diagnosis is faster when POC testing is used (Goodacre et al, 2011). Electrocardiogram testing and POC devices measuring cardiac troponin I levels have been used in a moving ambulance and showed good correlation to tests that were performed in the ED (Venturini et al, 2013). …”
Section: Emergency Departmentmentioning
confidence: 99%
“…In the study conducted by Venturini and colleagues, it was found that there was no significant difference between POCT devices operated in a moving ambulance and the measurement of cardiac troponin I levels obtained by POCT devices in the emergency department [22]. This confirms the practicality and utility of POCT in prehospital emergency contexts especially in future events of pre-hospital myocardial infarction.…”
Section: Current Practices On Poct In Pre-hospital Emergency Medicinementioning
confidence: 78%